LITERARY FEATURES OF DYSTOPIA IN“THE CHILDREN OF MEN” BY P.D.JAMES (World Bulletin of Social Sciences, 2024)
The aim of the study is to analyze the novel “The Children of Men” by female writer PD James in accordance with the main literary features of dystopia. Dystopian literature was formed in the eighteenth century but became popular in the twentieth century. Apart from the political system, nowadays, dystopian novels display environmental and human health problems which become vital issues. This study is an attempt to reveal the importance of the psychology of characters, considering using psychological methods. This will help readers to explore the essential dystopian features, of the work of P.D.James, studying infertility issues.